Sleep duration and risk of high blood pressure in Thai adolescents: the Thai National Health Examination Survey V, 2014 (NHES-V) - Kwanchai Pirojsakul; Wichai Aekplakorn; Sirinapa Siwarom; Witchuri Paksi; Pattapong Kessomboon; Nareemarn Neelapaichit; Suwat Chariyalertsak; Savitree Assanangkornchai; Surasak Taneepanichskul (BMC, 2022)
Abstract Background Sleep duration has been proposed to be associated with high blood pressure. However, nationwide studies regarding this association in adolescents remain limited. This study aimed to explore the national prevalence of high blood pressure among Thai adolescents and to determine the association between sleep duration and high blood pressure. Methods Data from adolescents aged 10-19 years from the Thai National Health and Examination Survey V were included. We collected demographic data (including age and gender), height, weight, waist circumference, blood pressure, fasting blood chemistries and sleep duration data. Sleep durations were categorized as short, normal or long for each age group based on the United States National Sleep Foundation's recommendations. High blood pressure was diagnosed using the 2017 guidelines of the American Academy of Pediatrics. Factors associated with high blood pressure were analyzed using multivariate logistic regression. Results A total of 3505 adolescents (1785 female) were included. The prevalence of high blood pressure was 9.4% (95% CI 8.5-10.4%). The high blood pressure group had higher BMI z-score, LDL-C, triglyceride and lower HDL-C than the normotensive group. In the multivariate analysis, BMI z-score, LDL-C and HDL-C were independently associated with high blood pressure. However, there was no association between sleep duration and high blood pressure. Conclusions High blood pressure risk was increased in adolescents with high BMI z-score. Neither short nor long sleep duration was associated with an increased risk of high blood pressure.